Rice Husks as Green Adsorbents for Removal of Anionic Dyes: Kinetic, Isotherm and Thermodynamic Adsorption Studies - Nur Ahmad; Neza Rahayu Palapa; Tarmizi Taher (Indonesian Journal of Material Research, 2023)
Rice husk, a green adsorbent, was used for procion red adsorption. Analysis with BET, XRD, FTIR, and SEM confirmed the formation of rice husk. The results indicate that rice husk is more porous and has a rougher surface. The surface of the rice husk has a non-uniform shape and uneven morphology. The pore of rice husk is critical to the adsorption process of procion red. The procion red will enter the pore of the rice husk to make an interaction. The rice husk has a surface area, pore volume, and pore diameter of 7.08 m2/g, 0.011 cc/g, and 3.14 nm, respectively. The vibrational peak at 3448 1620, 1103, and 794 cm−1. the XRD powder patterns of rice husk characterization diffraction peak at 2θ 23°. Rice husk’s adsorption system for procion red removal follows PSO kinetic and Freundlich isotherm models with a maximal removal capacity of 158.730 mg/g. This study sheds light on the effectiveness of rice husk as an adsorbent for procion red contaminants.